Impact of corporate social responsibility on organization performance of bank industry in sri lanka - Thilan malinga de silva, H. (University of Jaffna, 2016)
Nowadays Corporate Social Responsibility (CSR) is the most significant factor for the organization and it is directly affected to performance of the organizations. CSR realizes the responsibility of organization of related parties and the concept of CSR became to the th world of the 20 century as a result of industrial revolution. The key objective of organizations is to maximize the profit and in the case of CSR, organizations are avoided that key objective and try to minimize the gap between organization expectations and stakeholder's expectations. CSR helps to enhance competitive advantages of organizations and through that creates long term sustainability for organizations and also it avoids negatives and creates positives for organizations. CSR is one of the business strategy and that mitigate potential risks involve with the organizations. This study aims to identify the impact of the CSR on organization performance of bank industry in Sri Lanka. There are various factors influence on the organization performance and this study implements to know whether CSR has a real impact on organization performance. On the other hand, still companies don't know what proportion of CSR is to be maintained and what kind of CSR is to be done to gain more and thereby Objectives of the study are set to answer for those problems. Additionally, this study is providing the theoretical base on CSR and organization performance and through that analyse the relationship between CSR and organization performance. To achieve objectives of the study, quantitative approach has used with 72 respondents and the results are indicated that there is a significant positive correlation between CSR and organization performance of bank industry in Sri Lanka and also CSR positively impact on the organization performance of bank industry in Sri Lanka.
Keywords: CSR; Organization performance